Antifungal drug usage in haematologic patients during a 4‐year period in an Asian university teaching hospital. Issue 5 (14th May 2013) - Chan, T. S. Y.; Hwang, Y.‐Y.; Gill, H.; Cheung, W. W. W.; Tse, E.; Leung, A. Y. H.; Chim, C.‐S.; Lie, A. K. W.; Kwong, Y.‐L.
Abstract Background Invasive fungal disease (IFD) is an important problem complicating the therapy of haematologic patients. Aim This study aimed to provide data on the epidemiology of IFD in an Asian teaching hospital, as well as the prescription practice of antifungal drugs. Method We conducted a retrospective review of 275 haematologic patients who were prescribed antifungal drugs in a 4‐year period (2007–2010), of whom 130 (47%) had undergone haematopoietic stem cell transplantation. Results Antifungal prophylaxis with either fluconazole or itraconazole was given in 214 patients (78%). There were 414 prescriptions of antifungal drugs (including liposomal amphotericin B, voriconazole, caspofungin, micafungin, anidulafungin), of which 361 prescriptions were empirical. There were 14 patients with proven IFD, 11 of whom had breakthrough infection while on itraconazole prophylaxis. Interestingly, seven of these cases were due to infection by itraconazole‐sensitive candida. Conclusion These results provide important epidemiologic data necessary for the formulation of strategies for prevention and treatment of IFD in Asian patients.